Role of the Insulin-Like Growth Factor I/Insulin Receptor Substrate 1 Axis in Rad51 Trafficking and DNA Repair by Homologous Recombination - Trojanek, Joanna (American Society for Microbiology, 2003)
The receptor for insulin-like growth factor I (IGF-IR) controls normal and pathological growth of cells. DNA repair pathways represent an unexplored target through which the IGF-IR signaling system might support pathological growth leading to cellular transformation. However, this study demonstrates that IGF-I stimulation supports homologous recombination-directed DNA repair (HRR). This effect involves an interaction between Rad51 and the major IGF-IR signaling molecule, insulin receptor substrate 1 (IRS-1). The binding occurs within the cytoplasm, engages the N-terminal domain of IRS-1, and is attenuated by IGF-I-mediated IRS-1 tyrosine phosphorylation. In the absence of IGF-I stimulation, or if mutated IGF-IR fails to phosphorylate IRS-1, localization of Rad51 to the sites of damaged DNA is diminished. These results point to a direct role of IRS-1 in HRR and suggest a novel role for the IGF-IR/IRS-1 axis in supporting the stability of the genome.